Theory and application of augmented eccentric loading - Moore, C. A.; Schilling, B. K. (Strength and Conditioning Journal, 2005)
The method of utilizing augmented eccentric loading (AEL) during resistance exercise is still relatively new. The authors review the AEL literature and provide some guidelines for implementing AEL into the training program.